Association of Dietary Fiber Intake With Myocardial Infarction and Stroke Events in US Adults: A Cross-Sectional Study of NHANES 2011–2018 - Dong, Weiwei; Yang, Zhiyong (Frontiers in Nutrition, 2022)
Abstract: This study aimed to detect dietary fiber intake and its association with nonfatal cardiovascular/cerebrovascular events (myocardial infarction and stroke) in adults in the United States. This cross-sectional study obtained data from the 2011–2018 National Health and Nutrition Examination Survey database. Using multivariate logistic regression, we compared dietary fiber intake across demographics and detected an association between dietary fiber intake and patient-reported nonfatal myocardial infarction and/or stroke events. We enrolled 8,872 participants (mean dietary fiber intake, 17.38±0.22 mg/d). The weighted prevalence of nonfatal cardiovascular/cerebrovascular events was 5.36%, which decreased with higher dietary fiber intake (nonfatal cardiovascular/cerebrovascular events: Tertile1, 6.50%; Tertile2, 5.45%; Tertile3, 4.25%). Higher fiber intake indicated a stable negative association with nonfatal cardiovascular/cerebrovascular events in the multivariate logistic regression analysis, weighted generalized additive model, and smooth curve fitting. Interaction tests showed no significant effect of demographic, socioeconomic, and disease status on the association between dietary fiber intake and nonfatal cardiovascular/cerebrovascular events. Dietary fiber intake was far below the recommended amount. Higher dietary fiber intake was associated with a lower prevalence of nonfatal cardiovascular/cerebrovascular events.